1981
DOI: 10.21273/jashs.106.5.613
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supplemental HPS Lighting during Propagation on Rooting and Quality of ‘White Marble’ Cut Chrysanthemums1

Abstract: Supplemental high pressure sodium (HPS) night lighting during propagation increased early growth and rooting of Chrysanthemum morifolium Ramat. cv. White Marble cuttings planted in October, and early growth only in cuttings planted in January. The results depended on the ambient light conditions and the level of supplemental HPS irradiance. Flower quality was enhanced by the supplemental light treatments only in the October plantings. Improving ambient light conditions as the crop developed apparently compensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Those effects of supplemental irradiation during rooting the LD are in partial conflict with results of previous studies (13,14) which showed a strong influence of increasing irradiance during LD in reducing days to flower, but no significant effect as a result of rooting irradiation treatments. The present results do, however, correspond with other studies (11) which have shown that rooting irradiation treatments are effective in hastening flowering under conditions of low, natural irradiance.…”
Section: Resultssupporting
confidence: 87%
“…Those effects of supplemental irradiation during rooting the LD are in partial conflict with results of previous studies (13,14) which showed a strong influence of increasing irradiance during LD in reducing days to flower, but no significant effect as a result of rooting irradiation treatments. The present results do, however, correspond with other studies (11) which have shown that rooting irradiation treatments are effective in hastening flowering under conditions of low, natural irradiance.…”
Section: Resultssupporting
confidence: 87%
“…The supplemental irradiation during winter is predicted to decrease time to flower by 3 days, have no effect on shoot length, and increase flower area by 13%. Publications on the use of supplemental lighting have listed similar responses (4,5,17,18,20). In the summer, decreasing day and night temperature is predicted to decrease time to flower by 10 days, decrease stem length 2 cm, and increase flower area by 80%.…”
Section: R Esults and Discussionmentioning
confidence: 95%
“…Root growth of Aphelandra squarrosa was improved by the addition of dolomite to rooting media, but subsequent plant growth after transplant ing into pots was unaffected (1). Supple mentary lighting during rooting increased root grade and subsequent growth of chrysanthe mum cuttings (6). The cost of heating, how ever, may not be justified if subsequent plant growth does not increase sufficiently from the enhanced root growth.…”
mentioning
confidence: 99%